Satire Pada Puisi “Sajak Seonggok Jagung” Karya W. S. Rendra: Kajian Stilistika - Lolita, Asri (Kajian Linguistik dan Sastra, 2024)
This study aims to analyze stylistics in revealing satire in the poem "Sajak Seonggok Jagung" by W.S. Rendra. Stylistics, as a branch of linguistics that examines language style, is used to explore how linguistic elements such as diction, figurative language, repetition and parallelism, as well as syntactic structures, contribute to constructing the meaning of social criticism in the form of satire within a poem. The research method employed is descriptive qualitative, with data collected through document studies and textual analysis. The results indicate that W.S. Rendra effectively employs diction with contrasting and symbolic nuances, as well as figures of speech such as irony, metaphor, and satire—which are prominently featured in this poem—to convey criticism. Additionally, repetition and parallelism are used to emphasize ideas. The use of simple and declarative syntactic structures further strengthens the delivery of messages in a straightforward and communicative manner. The conclusion of this study reveals that stylistics in poetry functions not only as a decorative linguistic element, but also as a medium for ideological expression that reflects social realities. These findings reinforce the position of poetry as a form of criticism that is both aesthetic and ethical. Abstrak Penelitian ini bertujuan untuk menganalisis penggunaan stilistika dalam mengungkapkan satire pada puisi "Sajak Seonggok Jagung" karya W.S. Rendra. Stilistika sebagai cabang ilmu bahasa yang mengkaji gaya bahasa digunakan untuk menelusuri bagaimana unsur-unsur kebahasaan seperti diksi, majas, repetisi dan paralelisme, serta struktur sintaksis dapat membangun makna kritik sosial berupa sindiran dalam sebuah puisi. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui studi dokumentasi dan analisis teks. Hasil penelitian menunjukkan bahwa W.S. Rendra secara efektif menggunakan diksi yang bernuansa kontras dan simbolik, majas seperti ironi, metafora, dan satire yang begitu dominan ditemukan dalam puisi ini untuk menyampaikan kritik, serta repetisi dan paralelisme untuk penekanan gagasan. Struktur sintaksis yang sederhana dan deklaratif turut memperkuat penyampaian pesan secara lugas dan komunikatif. Simpulan penelitian ini menunjukkan bahwa stilistika dalam puisi tidak hanya berfungsi sebagai hiasan bahasa, melainkan juga sebagai medium ekspresi ideologis yang merefleksikan realitas sosial. Temuan ini memperkuat posisi puisi sebagai bentuk kritik yang estetik sekaligus etis.